Failure investigation of gfrp water storage tank: a case study at IKBN Jitra, Kedah / Mohd Ruzaimi Mat Rejab, Shukur Abu Hasan and Hasnulfikri Mahbot - Mat Rejab, Mohd Ruzaimi; Abu Hasan, Shukur; Mahbot, Hasnulfikri (2006)
This paper described a failure investigation of 13,200 gallons GFRP water storage tank that had happened at Institut Kemahiran Belia Negara (IKBN) Jitra, Kedah. Based on the preliminary observation, the failure started at the outlet flange hole where the water propagated inside the tank's wall and cracking the laminated composites. Four standard tests have been performed to investigate either the GFRP material or other factors that caused the tank to burst. Then, comparisons have been made with SIRIM's standard testing on fabricating water storage tanks and the results show that the material passed the minimum requirements of the tests. At the end of the investigation, the major failure that had been concluded was that lite fabricator is not using a good 'hand-lay up' technique to manufacture GFR? water storage tank according to the design specifications. These investigation results will bring advantageous to the researchers and water tank fabricalors in seeking the proper fabrication of GFRP water storage tanks with high mechanical performance, very robust and safe to be used in the residential areas.